Measuring Competition Intensity; An Application to Air/HSR Transport Markets - Christiaan Behrens; Mark Leijsen (Tinbergen Institute, 2015)
We develop a method to measure the intensity of competition between firms. Our method, which we call the Best Response Measure (BRM), is related to the conduct parameter method, but avoids the main problems associated with that method. The BRM relies on a very general framework and limited data requirements. Moreover, we show that it provides valuable information in determining the relevant market. We illustrate how the BRM can be used in markets with imperfect substitutes and apply the method to aviation markets in the North Sea area. This also enables us to establish to what extent the high speed rail link between London and the European mainland affects the supply by air carriers.
Keywords: D22; D43; L10; L93; R41; 330; inter- and intramodal competition; aviation; spatial networks; high-speed rail